VÎRANÎ BABA’NIN FAKR-NÂMESİNDE TASAVVUFÎ UNSURLAR - ATALAN, Mehmet (Scientific Journal of Faculty of Theology, 2017)
Bektashîzm, started to acquire a shape in Anatolia beginning from XIV th century, has maintained its notion up to now forming their norms in XVI th century. As result of this effect, many poets and writers who reflected Bektashî norms in their literature works emerged. In XVI th century Vîrânî, was one of the Bektashî poets of this period. Virani’s work called Fakr-Nâme has been delt on mystic currents and it has been densened over religions and ethical subjects. In this work we can see original Islamic faith consisting from minimum Islam that is based on the commands of the Quran and the Sunne of the prophet Muhammed and which never changes from sect to the sect. The religions motifs that are the most urgent things are the principles of worship confederated muslims altogether.